ISSUES ON KPPS MEMBER RECRUITMENT AN ADMINISTRATIVE LAW AND CITIZENS’ PARTICIPATION RIGHTS PERSPECTIVE - Isroun Annas Ma'ruf; Erman I. Rahim; Abdul Hamid Tome (Qaumiyyah: Jurnal Hukum Tata Negara, 2026)
The recruitment of Voting Organizing Groups (KPPS) is a crucial stage in the implementation of the General Election, determining the quality of voting and vote counting at Polling Stations (TPS). Although regulated by General Elections Commission Regulation Number 8 of 2022, its implementation in the West Kota District of Gorontalo City still faces various administrative, technical, and participatory obstacles. This study aimed to analyze the problems of KPPS recruitment from an administrative law perspective and its implications for the protection of citizens' rights to participate. The study used an empirical juridical method with a statutory and sociological approach. The results showed that the main obstacles to KPPS recruitment include the use of prospective registrants' names in the Political Party Information System (SIPOL), obstacles in fulfilling health certificate requirements, and low public interest in becoming KPPS members. These problems indicate the suboptimal implementation of the principles of legal certainty, proportionality, openness, and good service in the recruitment process. Furthermore, these various obstacles impede citizens' rights to obtain equal opportunities to participate in governance. Therefore, strengthening administrative mechanisms, expanding access to public services, and improving KPPS recruitment governance are essential to ensuring democratic, professional, and integrity based elections. Abstrak Rekrutmen Kelompok Penyelenggara Pemungutan Suara (KPPS) merupakan tahapan penting dalam penyelenggaraan Pemilihan Umum yang menentukan kualitas pelaksanaan pemungutan dan penghitungan suara di Tempat Pemungutan Suara (TPS). Meskipun telah diatur dalam Peraturan Komisi Pemilihan Umum Nomor 8 Tahun 2022, pelaksanaannya di Kecamatan Kota Barat Kota Gorontalo masih menghadapi berbagai kendala administratif, teknis, dan partisipatif. Penelitian ini bertujuan menganalisis problematika rekrutmen KPPS dalam perspektif hukum administrasi serta implikasinya terhadap perlindungan hak partisipasi warga negara. Penelitian menggunakan metode yuridis empiris dengan pendekatan peraturan perundang-undangan dan pendekatan sosiologis. Hasil penelitian menunjukkan bahwa hambatan utama rekrutmen KPPS meliputi pencatutan nama calon pendaftar dalam Sistem Informasi Partai Politik (SIPOL), kendala pemenuhan persyaratan surat keterangan kesehatan, serta rendahnya minat masyarakat untuk menjadi anggota KPPS. Permasalahan tersebut menunjukkan belum optimalnya penerapan asas kepastian hukum, proporsionalitas, keterbukaan, dan pelayanan yang baik dalam proses rekrutmen. Selain itu, berbagai hambatan tersebut berimplikasi pada terhambatnya hak warga negara untuk memperoleh kesempatan yang sama dalam berpartisipasi pada penyelenggaraan pemerintahan. Oleh karena itu, diperlukan penguatan mekanisme administrasi, peningkatan akses layanan publik, dan perbaikan tata kelola rekrutmen KPPS guna menjamin efektivitas penyelenggaraan pemilu yang demokratis, profesional, dan berintegritas.